Exome Sequencing as a Diagnostic Tool for Pediatric‐Onset Ataxia. Issue 1 (13th November 2013) - Sawyer, Sarah L.; Schwartzentruber, Jeremy; Beaulieu, Chandree L.; Dyment, David; Smith, Amanda; Chardon, Jodi Warman; Yoon, Grace; Rouleau, Guy A.; Suchowersky, Oksana; Siu, Victoria; Murphy, Lisa; Hegele, Robert A.; et al.
ABSTRACT Ataxia demonstrates substantial phenotypic and genetic heterogeneity. We set out to determine the diagnostic yield of exome sequencing in pediatric patients with ataxia without a molecular diagnosis after standard‐of‐care assessment in Canada. FORGE (Finding Of Rare disease GEnes) Canada is a nation‐wide project focused on identifying novel disease genes for rare pediatric diseases using whole‐exome sequencing. We retrospectively selected all FORGE Canada projects that included cerebellar ataxia as a feature. We identified 28 such families and a molecular diagnosis was made in 13; a success rate of 46%. In 11 families, we identified mutations in genes associated with known neurological syndromes and in two we identified novel disease genes. Exome analysis of sib pairs and/or patients born to consanguineous parents was more likely to be successful (9/13) than simplex cases (4/15). Our data suggest that exome sequencing is an effective first line test for pediatric patients with ataxia where a specific single gene is not immediately suspected to be causative.